Oxyphenbutazone in Plastic Surgery - Joya Chowdhury (Indian Journal of Plastic Surgery, 1974)
To summarise, a preliminary report of acontrolled trial with Oxyphenbutazone in 100 cases undergoing plastic surgery is presented and the evaluation assessed in three Grades and expressed in figures.